Impacts of initial conditions and model configuration on simulations of polar lows near Svalbard using Polar WRF with 3DVAR. (20th September 2021) - Xue, Jianjun; Bromwich, David H.; Xiao, Ziniu; Bai, Lesheng
Abstract: The impacts of initial conditions and model configuration on the simulations of polar lows (PLs) near Svalbard, the global "hotspot" for PL activity, were investigated using the Polar Weather Research and Forecasting (Polar WRF or PWRF) model and WRF three‐dimensional data assimilation (3DVAR). The well‐documented PL case presented by Sergeev et al., in 2017 from March 26, 2013 featuring in situ aircraft observations is revisited using PWRF and 3DVAR to identify the most suitable model configuration to simulate PLs. The simulation results using initial conditions from PWRF and 3DVAR cycling runs were compared with those of cold‐start experiments using reanalysis as the initial condition. For cycling runs, the impacts of initial conditions from synoptic observations together with satellite radiances were superior to the assimilation of synoptic data alone. Several additional experiments were undertaken to further refine the PWRF configuration by considering the horizontal resolution, analysis nudging, digital filter initialization, and two boundary‐layer and four microphysics schemes. Based on the chosen configuration of Polar WRF and 3DVAR from the case‐study, the monthly reanalysis mode with 3 hr time window cycling data assimilation and short‐term forecasts using PWRF alone were performed for March 2013 and the PLs that formed over the Nordic Seas were evaluated. Manual identification and verification of PLs were performed using thermal infrared satellite imagery and 10 m scatterometer winds. Overall, nine PLs were identified in addition to the case presented by Sergeev et al., in 2017. Both the case‐study and monthly simulation results show that the high‐resolution initial condition is the most important factor, but a reasonable forecast model configuration can help to improve the simulation performance. Satellite radiance data are very important for producing the high‐resolution initial conditions for Polar WRF to simulate PLs successfully; the best performance was obtained by assimilating both synoptic data and satellite radiances. Abstract : A case‐study (top: surface pressure from ERA‐Interim and satellite imagery; bottom: simulated surface pressure and outgoing long‐wave radiation) and month‐long simulations of polar lows near Svalbard during March 2013 were performed using Polar WRF alone, and Polar WRF with three‐dimensional data assimilation of solely synoptic observations as well as combined with satellite radiances. The best performance for simulations of polar low formation and evolution was obtained with cycling assimilation of both synoptic data and satellite radiances every 3 hr.